Efficacy of a long-term secondary prevention programme following inpatient cardiovascular rehabilitation on risk and health-related quality of life in a low-education cohort: a randomized controlled study. (February 2014) - Mayer-Berger, Wolfgang; Simic, Dusan; Mahmoodzad, Jawad; Burtscher, Ralph; Kohlmeyer, Martin; Schwitalla, Birgitta; Redaèlli, Marcus
Objective: The aim of this study was to evaluate the efficacy of a long-term secondary prevention programme following inpatient cardiovascular rehabilitation on cardiovascular risk and health-related quality of life in a cohort of middle-aged (≤58 years) coronary artery disease (CAD) patients of low educational level compared to usual care. Design and methods: The study included 600 patients with CAD, with 271 in the intervention group (IG) and 329 in the control group (CG). The average age was nearly 50 years in both groups, nearly 90% were male, and 77% had less than 10 years of school education. No significant differences existed between the groups at baseline. Both groups had a 3-week comprehensive cardiovascular inpatient rehabilitation programme at the beginning, the intervention consisted of one further rehabilitation session in hospital after 6 months and regular telephone reminders over a period of 36 months. Analyses were conducted on an intention-to-treat basis. To evaluate the individual risk level, we used the PROCAM score and intima-media thickness (IMT) was measured at the common carotid artery on both sides following international standards. Health-related quality of life was assessed with the EUROQOL and HADS. Results: Patients in the IG showed better 3-year risk profile outcomes. The PROCAM score increased by 3.0 (IG) and by 3.7 (CG) from the beginning to after 3 years ( p  > 0.05 intention-to-treat). The average IMT increased by 0.04 mm in the CG and was reduced by 0.03 mm in the IG ( p  = 0.014 for the difference). The IG had a significant improvement in health-related quality of life. Mortality, myocardial infarction, and stroke were not different although 'other cardiac events' (cardiac surgery or intervention) were significantly lower in the IG than the CG patients ( p  < 0.05). Conclusion: This long-term secondary prevention programme with inpatient rehabilitation at the beginning and telephone reminder for a 3-year period was successful. There were significant differences in health-related quality of life between the IG and CG, despite the relatively positive outcomes in the CG. In this low-education (predominantly male), middle-aged cohort, the positive impact on cardiovascular risk was pronounced in the high-risk subgroup (PROCAM 10-year risk 10–40%).